PENGARUH MODEL KOOPERATIF TIPE THINK PAIR SHARE (TPS) DISERTAI LKS BERNUANSA MIND MAP TERHADAP KOMPETENSI BELAJAR BIOLOGI SISWA DI KELAS X MAN 3 KERINCI - Hastutin, Sri Yuni; Ahda, Yuni; Lufri, Lufri (Kolaboratif, 2014)
This research was aimed at explaining the difference between learning achievement of the students taught by using TPS cooperative model assisted with Mind Map worksheet and those taught by using conventional method viewed from previous knowledge in class X of MAN 3 Kerinci. This was a quasi experimental. The population of the research was the students in class X of MAN 3 Kerinci registered in Academic Year 2012/2013. They were distributed into three classes XA, XB and XC. This research applied factorial block 2x2 design. Based on the result of the research, it was found that the Biology learning achievement of the students taught by using TPS cooperative model assisted with Mind Map Worksheet was better than that of students taught by using conventional method. It could be seen from the students’ average score in the experimental class which was 74,28, and in the control class which was 61,97. Learning achievement of the students having high previous knowledge taught by using TPS cooperative model assisted with Mind Map Worksheet was better than that of students taught by using conventional method in which the average score of the students in the experimental class was 80,41 and in the control class was 67,81. Learning achievement of the students having low previous knowledge taught by using TPS cooperative model assisted with Mind Map Worksheet was better than that of students taught by using conventional method in which the average score of the students in the experimental class was 67,14 and in the control class was 54,02. There is no interaction between TPS type of cooperative learning that includes Mind Map type of LKS to the Biology student’s learning outcomes.